PENINGKATAN KINERJA UMKM JANGGELAN DI KABUPATEN PACITAN MELALUI INTRODUKSI TEKNOLOGI PRODUKSI DAN MANAJEMEN KEUANGAN - Wiwit Rahayu; Dwi Ishartani; Nuning Setyowati (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2016)
”Janggelan” (Mesona palustris BI) that known by the name of Black Cincau is one of the plant species in Indonesia are grown widely in Pacitan, especially in Bandar sub district. “Janggelan” in Bandar subdistrict has good prospects to be developed because a lot of production and marketing is widespread. This opportunity was captured by residents in the “Jeruk Village”, Mr. Suyanto who processing wet “janggelan” into dry “janggelan” with the business name "Suyatno Janggelan" and Mr. Haris Kuswanto who processing “dry janggelan” become Cincau with the business name "Cincau Lestari". Problems encountered in the development of “Janggelan Business” are limited means of production, the production process is not suitable to the standards of food processing and financial management is not well ordered. Activities were undertaken aim to improve the performance of both SMEs partners. Activities include training of the Good Manufacturing Process (GMP), practical bookkeeping training and the introduction of production technology in the form of janggelan chopper machine, stainless steel drum for cooking “janggelan”, and the generator as a power source for a mechanical stirrer. From this activity, SMEs partners can increase the production and quality of products that suitable to the standards of Good Manufacturing Process, and have the financial records. At the end, this activity can increase revenues of SMEs partner.Keywords: “janggelan”, the performance of SMEs, production technology, financial management